182k views
0 votes
Simplify (4x − 6) + (5x + 1).

User Dryniex
by
5.2k points

2 Answers

2 votes

Answer:


\displaystyle =9x-5

Explanation:


\displaystyle 4x-6+5x+1

Group like terms.


\displaystyle 4x-6+5x+1

Add the numbers from left to right.


4+5=9


9x-6+1

Add and subtract numbers from left to right to find the answer.


6-1=5

It change to postive to negative sign.


\displaystyle=9x-5, which is our answer.

User Srikanth P
by
5.1k points
1 vote

Answer:

The simplified form is 9x - 5

Explanation:

It is given an expression in variable x

(4x − 6) + (5x + 1).

To find the simplified form

(4x − 6) + (5x + 1). = 4x − 6 + 5x + 1

= 4x + 5x - 6 + 1

= 9x -5

Therefore simplified form of given expression (4x − 6) + (5x + 1) is,

9x - 5

User Kstaruch
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.